The University as a tool for knowledge of Dentistry students on bioethical topics (Research, Society and Development, 2023)
The appreciation of bioethics as part of the ethical-humanistic improvement of dental surgeons has become increasingly evident. In this sense, this research aimed to verify the perception of information that dentistry students at the Federal University of Pernambuco have about bioethical dilemmas, also measuring the percentage of participation of university education in the development of this knowledge. For this, a semi-structured questionnaire was applied, using a Google Forms form, to which participants received a link via email address or WhatsApp application, using convenience sampling obtained by the “snowball” methodology. Students enrolled in the UFPE dentistry course took part in the research, excluding those who had left college. The sample was made up of 65 students, 80% of whom were female, with the 3rd and 5th periods having the highest number of participants. The results demonstrated a balanced perception of knowledge among students on the topics indicated in the questionnaire, with more than 50% reporting knowing 8 of the 10 bioethical topics. The university (93.8%), social networks (53.8%) and high school (41.5%) were the main sources indicated for gaining knowledge. It can be concluded that the university's participation and contribution to the construction of students' knowledge on bioethical topics is relevant, although it is not the only source of information about them.